2019
DOI: 10.1111/jofo.12298
|View full text |Cite
|
Sign up to set email alerts
|

Precise direct tracking and remote sensing reveal the use of forest islands as roost sites by Purple Martins during migration

Abstract: la conservaci on del ciclo anual completo de Progne subis y otras especies migratorias con poblaciones en disminuci on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Of these 238 birds, 200 tags were retrieved (22% of tags deployed) and 159 tags had data on them (80% of tags retrieved), although data did not always cover entire migration periods. Occasionally, authors using GPS-archival tags gave reasons for low return rates including low expected survival of the species (Fournier et al 2019) or vehicle mortality and movement out of the study site (Pagel et al 2020). Others found a lower retrieval rate of tagged birds compared to only-banded birds (12% vs. 25–48%; Lavallée et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Of these 238 birds, 200 tags were retrieved (22% of tags deployed) and 159 tags had data on them (80% of tags retrieved), although data did not always cover entire migration periods. Occasionally, authors using GPS-archival tags gave reasons for low return rates including low expected survival of the species (Fournier et al 2019) or vehicle mortality and movement out of the study site (Pagel et al 2020). Others found a lower retrieval rate of tagged birds compared to only-banded birds (12% vs. 25–48%; Lavallée et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The intraindividual variability we found for purple martins is more similar to broad, within-individual variation recently shown for some shorebirds (Senner et al, 2019;Verhoeven et al, 2019), than to data reported for nocturnally migrating songbirds. Purple martins are diurnal migrants that roost in large flocks during stopovers across migration (Brown and Tarof, 2013), and may use island-like habitats for stopover (Fraser et al, 2017;Fournier et al, 2019). Large social aggregations and suitable stopover habitat are unevenly distributed across a migratory landscape, thus martin stopover decisions may be influenced by these social factors which could contribute to variation in their individual timing.…”
Section: Discussionmentioning
confidence: 99%
“…We used the purple martin ( Progne subis ) as a model species for colonial aerial insectivores because they have central nests or roosts at throughout most of the year and they are one of the largest swallows, allowing them to be tracked using recently-miniaturized GPS biologgers [ 19 , 20 ]. Given that aerial insectivores are a rapidly declining avian guild [ 21 – 23 ], and there is no consensus on the main cause of decline [ 9 , 24 , 25 ], understanding their year-round habitat requirements is critical for developing management practices that would contribute to conservation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%